From learner to therapist: a story of transcendence and transformation - Hester G Pretorius; Anne-Marie Lydall; Rahima Mohamed-Patel; Antoinette Rikhotso; Grant W Evans (AOSIS, 2005)
Therapeutic interventions are guided as much by a therapist's philosophy as they are by an understanding of psychological and therapeutic principles. Opsomming Terapeutiese intervensies word net soveel gerig deur 'n terapeut se lewensfilosofie, as deur 'n begrip van sielkundige en terapeutiese beginsels. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.